Evaluation from a Gender+ Perspective as a Key Element for (Re)gendering the Policymaking Process. (2nd January 2017) - Bustelo, María
ABSTRACT: Feminist scholars have challenged the neutrality of policymaking processes and the outputs resulting from these processes. However, some elements of policymaking have not been studied as well as others. In this article I explore the concept of evaluation from a gender+ perspective as an essential step for a complete gender mainstreaming strategy, which can help to identify gender issues that should be integrated into the content of evaluated policies and to ensure gender does not get lost in the policymaking process. This exploration is carried out by relying on feminist policy and evaluation studies.